Zinc as an Essential Micronutrient and Its Positive Impact in Improving Body Immunity to Infection Through Nutritional Approach: A Literature Review - Permataputri, Chy’as Diuranil Astrid (Journal of Diverse Medical Research: Medicosphere, 2024)
Background: Zinc is an essential mineral involved in various biological functions, including the regulation of the immune system. Zinc deficiency can lead to impaired immune function, increased susceptibility to infections, and delayed healing of diseases.  Methods: We searched the Pubmed and Google Scholar databases using relevant keywords such as “zinc”, “zinc supplementation”, “essential micronutrients”, "immune system”, and "infectious diseases."  Discussion: The results of the study indicate that zinc supplementation significantly impacts individuals with zinc deficiency, particularly in enhancing the number and function of immune cells like T and B cells. However, in a healthy population with normal zinc levels, supplementation did not yield significant improvements in immune function.  Conclusion: Zinc is an essential micronutrient that plays a crucial role in enhancing the immune system, especially in individuals with deficiency. Further research is needed to better understand the mechanisms by which zinc supports immunity in a broader population.   Keywords: zinc, immune system, infectious diseases.